THE CONTRIBUTION OF HRD ORGANIZATIONS TO THE DEVELOPMENT OF STRATEGIC COMPETENCIES THROUGH THE IMPLEMENTATION OF LEARNING ORGANIZATION CONCEPTS - Acep Sukandi; Hardy Zhang (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2025)
ABSTRACT This study examines how Human Resource Development (HRD) organizations contribute to developing members’ strategic competencies by implementing learning organization concepts. Focus is placed on the HRD Communication Forum in the GIIC–KITIC Industrial Area of Deltamas—a collaborative platform for HR practitioners across various companies. Using a quantitative explanatory design, data were collected from active members via structured questionnaires. The research model incorporates HRD organizational contribution as the independent variable, organizational learning as a mediating variable, and strategic competency development as the dependent variable. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results indicate that HRD organizational contributions significantly and positively affect organizational learning, which in turn enhances members’ strategic competencies. Furthermore, organizational learning partially mediates the relationship between HRD contribution and strategic competency development. These findings confirm that HRD forums can operate as effective non-formal learning organizations when learning principles are systematically embedded. Theoretically, this study strengthens the integrative link between HRD and learning organization theory in non-formal professional settings, while offering practical insights for human resource development in industrial zones. Keywords: Human Resource Development; Learning Organization; Strategic Competency; Organizational Learning; HRD Forum JEL Classification        : J24, M14, O15